(untitled) (BISTUA Revista de la Facultad de Ciencias Básicas, 2025)
Botrytis cinerea is a plant pathogen that affects a wide range of plants and is responsible for severe economic losses in more than 200 crops worldwide. Although the use of fungicides is the most common strategy for its control, the genetic plasticity of this fungus allows it to develop resistance. Consequently, biological control has gained ground as an alternative or complementary approach to fungicides. In this respect, the genus Trichoderma is the most extensively studied group with the greatest potential for biological control of B. cinerea. Therefore, the search and study of native Trichoderma strains with biocontrol potential is a line of interest for the local and regional agricultural sector. This study reports the in vitro investigation of the biocontrol capacity of a commercial product, in comparison with the antagonistic power of two native strains isolated from soils in the agricultural areas of the municipalities of Pamplona (TN01) and Bucarasica (TN02), in Norte de Santander. Morphological characterisation determined that both strains are taxonomically located in the Viride clade of the genus Trichoderma. The growth rate and the percentage of radial growth inhibition (PICR) of the antagonists were determined using the dual culture technique. The results indicated that TN01 was the strain with the highest potential to be used as a biological controller of Botrytis spp. This strain showed the highest apical growth rate and achieved a PICR of 80% at the end of the experiment, exceeding that achieved by the commercial reference product. Conversely, strain TN02 exhibited a diminished antagonistic capacity, with a PICR of 55% after a 12-day period. This observation suggests the potential for the autochthonous strain TN01 to be evaluated under cultivation conditions.